The sociological imagination in studies of communication, information technologies, and media: CITAMS as an invisible college - Quan-Haase, A.; Boulianne, Shelley; Harper, M.-G. (My University, 2020)
Sociology is an interdisciplinary field that has much to offer. The sociological imagination as Mills (1970/2000) proposed it comprises ‘vivid awareness of the relationship between personal experience and the wider society’ (p. 5). While much debate surrounds the idea of the sociological imagination, it is often understood as an outlook, one that steers us away from thinking routinely about our everyday lives and encourages us instead to re-examine daily routines and everyday practices with a critical lens (Quan-Haase & Tepperman, 2018). This makes the sociological imagination a particularly fruitful framework to draw from when examining communication and information technologies, digital media, and legacy media. ICTs surround us all and have become a commonplace element of daily life in many parts of the world. This is not unique to the Global North; ICTs and their impacts and values are equally important to the Global South, making them a unifying factor globally.
Keywords: information technologies; sociological imagination; communication; CITAMS; media